INVESTIGATION OF OPTICAL PROPERTIES OF DUSTY PLASMA IN CAPACITIVE RADIO FREQUENCY DISCHARGE OF ARGON - Jumabekov, A. N.; Orazbaev, S. A.; Kodanova, S. K.; Ibraimov, K. M.; Dosbolayev, M. K.; Dzhumagulov, M. N.; Danyarov, T. T.; Ramazanov, T. S.; Azharonok, V. V.; Filatova, I. I. (Recent Contributions to Physics, 2009)
In present paper the results of the experimental investigations of optical properties of dusty plasma in capacitive radio frequency discharge were presented. The influence of dust component on intensity of spectral liens was shown on the basis of analysis of spatial spectra of radiofrequency discharge plasma. Results of present work can be basis in optical diagnostics of plasma of capacitive radiofrequency discharge.